Amino Acid New Insights and Roles in Plant and Animal - Asao, Toshiki; Asaduzzaman, Md (IntechOpen, 2017)
Amino Acid - New Insights and Roles in Plant and Animal provides useful information on new aspects of amino acid structure, synthesis reactions, dietary application in animals, and metabolism in plants. Section 1 includes chapters that describe the therapeutic uses, antiallergic effects, new aspects in the D-amino acid structure, historical background of desmosines, and stereoselective synthesis of ?-aminophosphonic acids. Section 2 presents the role of amino acids in plants, which includes new insights and aspects of D-amino acids, metabolism and transport in soybean, changes during energy storage compound accumulation of microalgae, and determination of amino acids from natural compounds. Section 3 describes the chapters on methodologies and requirement of dietary amino acids for Japanese quails, laying hens, and finishing pigs. The final chapter identifies potential importance of glutathione S-transferase activity for generating resistance to triclabendazole in Fasciola hepatica.